2018
DOI: 10.1016/j.bbamcr.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Novel short isoforms of adenylyl cyclase as negative regulators of cAMP production

Abstract: Here, we cloned a new family of four adenylyl cyclase (AC) splice variants from interleukin-1β (IL-1β)-transdifferentiated vascular smooth muscle cells (VSMCs) encoding short forms of AC8 that we have named "AC8E-H". Using biosensor imaging and biochemical approaches, we showed that AC8E-H isoforms have no cyclase activity and act as dominant-negative regulators by forming heterodimers with other full-length ACs, impeding the traffic of functional units towards the plasma membrane. The existence of these domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Upon heterodimerization, this may result in activation or dominant-negative inhibition, dependent on AC isoform composition of the tip domain and changing environmental stimuli to fine-tune cAMP levels. Dominant-negative heterodimer formation has previously been described for invertebrate soluble guanylate cyclase (GC) 70 , mammalian AC8 in vascular smooth muscle cells 71 and also ESAG4 of trypanosomes 33 . In agreement with the model, AC isoform diversity and non-redundancy at the flagellar tip 7 and differential expression of transcripts encoding AC isoforms in trypanosomes colonizing midgut, cardia or salivary glands 36 , 37 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Upon heterodimerization, this may result in activation or dominant-negative inhibition, dependent on AC isoform composition of the tip domain and changing environmental stimuli to fine-tune cAMP levels. Dominant-negative heterodimer formation has previously been described for invertebrate soluble guanylate cyclase (GC) 70 , mammalian AC8 in vascular smooth muscle cells 71 and also ESAG4 of trypanosomes 33 . In agreement with the model, AC isoform diversity and non-redundancy at the flagellar tip 7 and differential expression of transcripts encoding AC isoforms in trypanosomes colonizing midgut, cardia or salivary glands 36 , 37 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Such negative trend was not observed in pyramidal cortical neurons showing that a buffering effect did not affect the responses in these conditions (Castro et al, 2013). However, the buffering effect was clearly observed in vascular smooth muscle cells, with a statistically lower cAMP response in the cells expressing the biosensor at the highest level (Figure 5 in (Vallin et al, 2018)). Simulations using a model built from our biosensor recordings showed that this buffering effect is negligible in striatal medium-sized spiny neurons, in relation with the high turn-over of cAMP in this neuronal type (Yapo et al, 2017).…”
Section: Buffering Effectmentioning
confidence: 86%
“…6f). Dominant-negative heterodimer formation has previously been described for invertebrate soluble guanylate cyclase (GC) 85 , mammalian AC8 in vascular smooth muscle cells 86 and also ESAG4 of trypanosomes 31 .…”
Section: Discussionmentioning
confidence: 99%